The artist’s book: Working towards a collaborative methodology in art and design - Özmen, M. (Taylor and Francis, 2024)
The working methodologies of visual art and visual communication design are often distinctive and require different skill sets, even though art and design disciplines are similar in many ways. For instance, in exhibiting and promoting an artwork, a level of collaboration must be established between the visual artist and the visual communication designer, which demands interdisciplinarity. This chapter, firstly, addresses the interdisciplinarity of art and design by opening the historically maintained hierarchical structure among those disciplines into a discussion for a collaborative working methodology. The second part focuses on the artist’s book as a medium and as a significant space in exhibiting and promoting the artwork to build dialogue and collaboration through a case study of an actual artist’s book created by an artist and a designer in three steps of research, analysis, and production. © 2024 selection and editorial matter, Begüm Irmak, Can Koçak, Onur Sesigür and Nazan Haydari; individual chapters, the contributors.